Integrated Roles of Nursing Leadership and Social Work in Health Management: A Strategic Framework for Enhancing Patient Support Systems - A, Albishi,Hanan Mansour; Alzahrani, Ahmed Ali Saleh; Alqutayfi, Raniyah Abdulaziz; Meghas, Uthman Abdullah; Meghas, Munahi Abdullah; Aljuhani, Amani Faisal; alzahrani, Ibrahim Mousa Ibrahim; Abuzahera, Amani O.; Al-Mutairi, Ghazi Hamdan Humaidan; Al-Mutairi, Abdulaziz Saad; Altuwaylie, Samar Awadh (Journal of Posthumanism, 2024)
The increasing complexity of patient needs in contemporary healthcare systems necessitates a more integrated and interdisciplinary approach to care delivery. In particular, the roles of nursing leadership and social work have emerged as critical yet often underutilized components of patient support systems. While both professions address essential aspects of clinical and psychosocial care, a lack of structured collaboration often results in fragmented service delivery. This study aimed to develop and validate a strategic framework for the effective integration of nursing leadership and social work within healthcare management structures in Saudi Arabia. A mixed-methods research design was employed across eight healthcare institutions. Quantitative data were collected from 300 professionals, including nurses, social workers, and healthcare administrators, using structured questionnaires. Qualitative insights were gathered through 16 in-depth interviews and two focus groups. Structural equation modeling (SEM) using SmartPLS 4 was conducted to validate the relationships among leadership engagement, role clarity, communication quality, team coordination, and patient outcomes. The study revealed strong support for collaborative practices, with statistically significant relationships between leadership and improved communication, team-based coordination, and patient satisfaction. Readmission rates decreased by 7.7%, and continuity of care improved by 19.9% post-integration. The framework demonstrated strong internal consistency (Cronbach’s α > 0.86) and good model fit (SRMR = 0.062). The validated strategic framework offers a practical, evidence-based model for integrating nursing and social work in patient care systems. Its adoption has the potential to enhance patient outcomes, streamline care transitions, and foster a culture of interdisciplinary collaboration in healthcare institutions across Saudi Arabia and beyond.